Exposure to maternal cafeteria diets during the suckling period has greater effects on fat deposition and Sterol regulatory element binding protein-1c (SREBP-1c) gene expression in rodent offspring compared to exposure before birth - Vithayathil, M.A.; Gugusheff, J.R.; Ong, Z.Y.; Langley-Evans, Simon C.; Gibson, R.A.; Muhlhausler, B.S. (BioMed Central, 2018)
Background: While the adverse metabolic effects of exposure to obesogenic diets during both the prenatal and early postnatal period are well established, the relative impact of exposure during these separate developmental windows remains unclear. Objective: This study aimed to assess the relative contribution of exposure to a maternal cafeteria diet during pregnancy and lactation on body weight, fat mass and expression of lipogenic and adipokine genes in the offspring. Methods: Wistar rats were fed either a control chow (Control, n=14) or obesogenic cafeteria diet (CAF, n=12) during pregnancy and lactation. Pups were cross-fostered to another dam in either the same or different dietary group within 24 h of birth. Body weight, body fat mass and expression of lipogenic and adipokine genes in subcutaneous and visceral adipose tissues were determined in offspring at weaning and 3 weeks post-weaning. Results: Offspring suckled by CAF dams had a lower body weight (P<0.05), but ~2-fold higher percentage body fat at weaning than offspring suckled by Control dams (P<0.01), independent of whether they were born to a Control or CAF dam. At 6 weeks of age, after all offspring were weaned onto standard chow, males and females suckled by CAF dams remained lighter (P<0.05) than offspring suckled by Control dams, but the percentage fat mass was no longer different between groups. Sterol Regulatory Element Binding Protein-1c (SREBP-1c) mRNA expression was ~25% lower in offspring suckled by cafeteria dams in males at weaning (P<0.05) and in females at 6 weeks of age (P<0.05). Exposure to a cafeteria diet during the suckling period alone also resulted in increased adipocyte Peroxisome Proliferator Activated Receptor-γ (PPAR-γ) mRNA expression in females, and adiponectin and leptin mRNA expression in both sexes at weaning. Conclusions: The findings from this study point to the critical role of the suckling period for deposition of adipose tissue in rodents, and the potential role of altered adipocyte gene expression in mediating these effects.